Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe STAD Terhadap Hasil Belajar Siswa Kelas X Pada Mata Pelajaran Ekonomi Di SMAN 1 Lewolema Tahun Pelajaran 2025/2026 - Veronika Bopo Aran; Mudmainna Mudmainna; Margiana D.M.M Maran (Lembaga Riset dan Inovasi Almatani, 2026)
This study aims to determine the effect of implementing the Student Teams Achievement Division (STAD) cooperative learning model on the learning outcomes of Grade X students in Economics at SMAN 1 Lewolema in the 2025/2026 Academic Year. This research employed a quantitative approach with a descriptive method. The population consisted of all students in classes XA and XB, totaling 50 students. A saturated sampling technique was applied, in which the entire population was used as the research sample. Data were collected through questionnaires to measure the implementation of the STAD cooperative learning model and documentation to obtain students’ learning outcome data. The collected data were analyzed using simple linear regression with the assistance of SPSS version 24 at a 5% significance level. The results showed that the implementation of the STAD cooperative learning model was categorized as good and was able to enhance students’ activeness, cooperation, responsibility, and participation in the learning process. The simple linear regression analysis indicated that the STAD cooperative learning model had a positive and significant effect on students’ learning outcomes. This was evidenced by the t-value of 7.349, which was greater than the t-table value of 1.677, and a significance value of 0.000 < 0.05. Furthermore, the coefficient of determination analysis revealed that the STAD cooperative learning model contributed 52.9% to students’ learning outcomes, while the remaining 47.1% was influenced by other factors not examined in this study. Therefore, the implementation of the STAD cooperative learning model can serve as an effective alternative for improving students’ learning outcomes in Economics at SMAN 1 Lewolema.